Association Between c-Myc and Colorectal Cancer Prognosis: A Meta-Analysis - He, Wei-Ling; Weng, Xiang-Tao; Wang, Jue-Lian; Lin, Yong-Kai; Liu, Tian-Wen; Zhou, Qian-Yi; Hu, Yue; Pan, Yunbao; Chen, Xin-Lin (Frontiers in Physiology, 2018)
Background There is debate as to whether c-Myc predicts prognosis in colorectal cancer (CRC). In this study, we aimed to review the association between c-Myc and CRC prognosis. Methods Pertinent studies were identified by searching electronic databases and carefully reviewing the reference lists of pertinent studies until March 2016. The summary hazard ratio (HR) and corresponding 95% confidence interval (CI) were calculated to study the association between c-Myc and CRC prognosis. Results Eight cohort studies (including 7 studies about overall survival [OS] and 1 study about disease free survival [DFS]) were included. The pooled HR of OS was 1.13 (95% CI: 0.66–1.95). In subgroup analysis, no significant association between c-Myc and CRC prognosis was found in the studies either from Western countries (HR: 0.87, 95 % CI: 0.68–1.10) or Asian countries (HR: 1.89, 95 % CI: 0.62–5.77). HRs were 0.86 (95% CI: 0.38–1.94) and 1.57 (95% CI: 0.73–3.39) for the studies using univariate analysis and multivariate analysis, respectively. HR from the studies that examined DNA level was significantly different (HR: 2.05, 95% CI: 1.22–3.46); while that about RNA level or protein level was not significantly different. Conclusion c-Myc was not associated with CRC prognosis in this meta-analysis. However, the conclusion is preliminary and should be examined in future studies.